A new wall model for slip boundary conditions in dissipative particle dynamics. (17th April 2019) - Xu, Shaofeng; Wang, Q. Jane; Wang, Jiugen
Summary: Dissipative particle dynamics (DPD) for modeling complex flows requires proper boundary conditions to simulate the behavior of a wall‐bounded flow. Although most DPD simulations use the no‐slip boundary condition, slip should be considered for a more complete and realistic description of such flows. The present work suggests a new wall model, via a wall‐particle virtual velocity approach, to impose tunable partial‐slip boundary conditions while structuring a modified reflection mechanism to enforce the no‐slip boundary condition. The new wall model is validated through simulating the planar Poiseuille and Couette flows and implemented to investigate the wall slip status affected by the wall virtual velocity. Abstract : A new wall model is proposed to impose the partial‐slip boundary condition in dissipative particle dynamics. The wall model involves three layers of frozen particles for the walls, in combination with a modified bounce‐forward reflection method to reintroduce the penetrated particles back into the fluid region. The partial‐slip boundary condition is achieved by applying a virtual velocity α V and the tunability of partial slip can be obtained by adjusting the tuning parameter α.